Effects of polyphenol-rich seed foods on lipid and inflammatory markers in patients with coronary heart disease: a systematic review - Jia, Yatian; Wang, Hui; Fan, Wen; Lv, Jie; Niu, Qingmei; Zhu, Ruifang; Zhang, Qian (Frontiers in Nutrition, 2024)
Background: Coronary heart disease (CHD) is a prevalent cardiovascular condition, with its incidence and mortality rates steadily rising over time, posing a significant threat to human health. Studies have indicated that polyphenols exhibit a certain degree of protective effect against coronary heart disease. However, the findings regarding the impact of polyphenol-rich seed foods on patients with CHD have yielded inconsistent results. Objective: This study investigated the effects of polyphenol-rich seed foods on blood lipids and inflammatory markers in patients with coronary heart disease. Methods: The China National Knowledge Network, China Science and Technology Journal Database, China Biomedical Literature Database, Wanfang Database, PubMed, Cochrane Library, Embase, and Web of Science were searched for articles from the self-built database until March 16, 2024. The quality of the included studies was assessed using Edition 2 of the Cochrane Randomised Trials Risk Bias Tool, and data analysis was conducted using RevMan 5.4. Results: The study encompassed seven articles, with a total participation of 324 patients diagnosed with coronary heart disease. The study incorporated three seed foods abundant in polyphenols: Brazil nut, almond, and flaxseed. The meta-analysis findings revealed a significant reduction in triglyceride levels (MD = -20.03, 95% CI [-32.25, -17.44], P < 0.00001) among patients diagnosed with coronary heart disease who incorporated seed-based foods abundant in polyphenols into their diet regimen. Furthermore, a notable enhancement was observed in HDL cholesterol levels (MD = 3.14, 95% CI [1.55, 4.72], P =0.0001). Moreover, the type of intervention substance influenced the observed effects. The consumption of almonds has been demonstrated to significantly reduce total cholesterol (MD = -15.53, 95% CI [-21.97, -9.1], P < 0.00001) and LDL cholesterol (MD = -14.62, 95% CI [-20.92, -8.33], P < 0.00001) in patients diagnosed with coronary heart disease. Additionally, the incorporation of flaxseed into the diet has shown an enhanced effect on reducing C-reactive protein levels. Conclusion: The consumption of polyphenol-rich seed foods can moderately improve TG and HDL-C levels in patients with coronary heart disease, while incorporating flaxseed into their diet can effectively improve inflammatory markers.